The Influence of Workload and Reward on Employee Performance (Survey at PT. Bank Syariah Indonesia KCP Cianjur Employees) - Ananda Rizkia Kamal; Faizal Mulia Z; Sopyan Saori (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine how much influence the workload and reward provision have on the performance of employees of PT. Bank Syariah Indonesia Kxp Cianjur. Respondents in this study were 40 people aimed at employees of PT. Bank Syariah Indonesia Kcp Cianjur. This research method uses a quantitative method with a descriptive and associative approach. In this study, a normality test, simultaneous statistical test (F test) and partial statistical test (T test) were carried out. The results of this study indicate that there is a simultaneous positive influence between Workload, Reward Provision and Employee Performance, with a result of 60,556> 2.84 which means that the F Calculation value is greater than the F Table. Meanwhile, partially Workload has a positive and significant effect on Employee Performance, this is evidenced by the value obtained from the T Calculation result which is 5,587 greater than the T Table which is 1,687, with a significance value of 0.000 <0.05. And the provision of rewards has a positive and significant effect on employee performance, this is proven by the value obtained from the results of the T count, which is 5.109, which is greater than the T table, which is 1.687, with a significance value of 0.000 <0.05.